Controle da lanosidade, em pêssegos chiripá , com o uso de atmosfera controlada e etileno - Giehl, Ricardo Fabiano Hettwer (2006)
Experiments were performed aiming to study the effect of controlled atmosphere (CA) and exogenous ethylene treatment on both the post-storage ripening and mealiness (woolliness) occurrence, evaluated both visually and objectively by the free juice content in the flesh of Chiripá peach fruits. Furthermore, the effect of inhibiting the ethylene action either in the beginning or in the end of CA storage on the incidence of physiological disorders and on the physical and chemical quality were also evaluated. In the first experiment, carried out both in 2005 and 2006, we evaluated: [1] cold storage (CS 21.0 kPa O2 + <0.5 kPa CO2); [2] CA with 1.0 kPa O2 + 3.0 kPa CO2; and [3] CA with 2.0 kPa O2 + 8.0 kPa CO2. In 2005, fruits were stored during 25, 30, and 35 days at -0.5°C, whereas in 2006, storage was prolonged until 40 days. The second experiment evaluated the effect of exogenously applied ethylene in the storage room. The storage conditions were: [1] CS; [2] CS + exogenous ethylene (≈20 μL L-1); [3] CA (1.0 kPa O2 + 3.0kPa CO2); and [4] CA + exogenous ethylene. In the third trial, the effect of the ethylene action was assessed by the application of 1- methylcyclopropene (1-MCP - 900nL L-1), a potent inhibitor of the ethylene action. The treatments studied were: [1] CS + 1-MCP; [2] CA (2.0 kPa O2 + 8.0 kPa CO2); [3] CA + 1- MCP applied during the first 24 h of storage (P1); and [4] CA + 1-MCP applied during the first 24 h of post-storage ripening at 20°C (P2). As the storage period was increased, the free juice contents decreased, independently of the storage condition. The flesh juiciness decreased sharply until 2 days of post-storage ripening at 20°C, but increased again thereafter. This free juice restoration was both a storage period- and a storage condition-dependent process. CAstored fruits, especially in 2.0 kPa O2 + 8.0 kPa CO2, restored free juice contents faster. However, CS-stored fruits showed an abnormal pattern of ethylene synthesis, as the storage period was prolonged, a behavior that possibly led these fruits to restore their free juice contents to a lesser extend. Ethylene treatment during CS enhanced post-storage ethylene production and allowed fruits to restore juiciness at the same level as CA did. In addition to the ability of fruits in synthesize ethylene and to the effect of the presence of this gas, the ethylene action, during the post-storage ripening, was critical for the process of free juice restoration to occur. The application of 1-MCP, in the beginning of the CA storage, is the most promising technique for storing Chiripá peach fruits, because it allows both physical and chemical quality maintenance and avoids the dramatic decrease of flesh juiciness at the 2nd day after storage